Narrowband ultraviolet B treatment for psoriasis is highly economical and causes significant savings in cost for topical treatments. (1st November 2018) - Boswell, K.; Cameron, H.; West, J.; Fleming, C.; Ibbotson, S.; Dawe, R.; Foerster, J.
Summary: Background: Narrowband ultraviolet B (NB‐UVB) treatment for psoriasis is considered expensive. However, existing data are based on estimates and do not consider indirect cost savings. Objectives: To define the actual costs of NB‐UVB incurred by the service provider, as well as treatment‐associated cost savings. Methods: We performed data linkage of (i) comprehensive treatment records and (ii) prescribing data for all NB‐UVB treatment episodes spanning 6 years in a population of 420 000. We minimized data fluctuation by compiling data from four independent treatment sites, and using drug prescriptions unrelated to psoriasis as a negative control. Results: National Health Service Tayside spent an average of £257 per NB‐UVB treatment course (mean 257 ± 63, range 150–286, across four independent treatment sites), contrasting sharply with the estimate of £1882 used by the U.K. National Institute for Health and Care Excellence. The cost of topical treatments averaged £128 per patient in the 12 months prior to NB‐UVB, accounting for 42% of the overall drug costs incurred by these patients. This was reduced by 40% to £53 per patient over the 12‐month period following NB‐UVB treatment, while psoriasis‐unrelated drug prescription remained unchanged, suggesting disease‐specific effects of NB‐UVB. The data were not due to site‐specific factors, as confirmed by highly similar results observed between treatment sites operated by distinct staff. Finally, we detail all staff hours directly and indirectly involved in treatment, allowing direct translation of cost into other healthcare systems. Conclusions: NB‐UVB is a low‐cost treatment; cost figures currently used in health technology appraisals are an overestimate based on the data presented here. Creating or extending access to NB‐UVB is likely to offer additional savings by delaying or avoiding costly third‐line treatments for many patients.